Analysis of Cointegration and VECM of FDI, Labor Force, Government Expenditure and GDP in Indonesia (2005-2019) - Danang Indrajaya (International Journal of Economics Development Research (IJEDR), 2021)
This paper studied the effect of labor force, government expenditure and FDI on GDP of Indonesia (2005-2019) by cointegration analysis and VECM. In the short-term, GDP, labor force and government expenditure significantly affect GDP of Indonesia, while FDI does not significantly affect Indonesia’s GDP. However, in the long term, GDP, labor force, government expenditure and FDI have a significant affect GDP of Indonesia. The government must ensure that there are no shocks in GDP, labor force, government expenditure and FDI of Indonesia. Because any shocks that occur in these variables will also have an impact on the GDP of Indonesia.   Keywords: GDP, Labor Force, FDI, Government Expenditure